The role of online communities in science teachers' continuous professional development - Ioannou, Andri; Kyza, Eleni A.; Georgiou, Yiannis (My University, 2012)
We report on the creation of online teacher communities within the framework of the PROFILES project, aiming at teachers' professional development in inquiry-based science education. It was anticipated that teachers would form active communities of practice to support the integration of inquiry and new technologies into their lessons. An exploratory approach was used to trace the local needs of the teachers and to identify the role of the online communities to support continuous professional development. ISLS.
Keywords: Communities of practice; Continuous professional development; Inquiry-based science; New technologies; On-line communities; Professional development; Science teachers; Teacher community; Online systems; Professional aspects; Websites; Education